068 The effective management of idiopathic intracranial hypertension delivered by in-person and virtual group consultations. Issue 6 (27th May 2022) - Wong, Sui; Barrow, Natasha; Hall, Kimberley; Gandesha, Prianka; Manson, Alison
Abstract : Background: In response to the rising incidence of IIH and service pressures, we set out to develop a group consultation(GC) service for IIH. Method: Iterative, co-designing(with patients) a bespoke GC, i.e. clinical reviews in a group setting. Outcomes measured: patient satisfaction, self-perceived health literacy, successful implementation of GC. Results: Eight in-person GCs delivered: once-monthly(Oct-Dec 2019), then twice-monthly(Jan-Feb 2020). Feedback from 49/53: 100% felt more satisfied and heard; 100% felt more involved in decision making; 98% had a better understanding of their condition; 96% felt more able to cope with their condition and keep themselves healthy; 94% rated this as a positive experience; 90% reported improved access and more time with their clinician compared to existing 1:1 appointments. Since Sept 2020 (in response to COVID-19 pandemic) we have delivered once-weekly virtual GC (18 to date). Feedback median scores: patient satisfaction 9.5/10; being listened to by clinician 10/10; involved by clinician in treatment decisions 10/10; clinician explanation of treatment 10/10; opportunity to discuss condition or treatment 10/10). Conclusions: GC is safe and effective for IIH and preferred in our cohort. This allowed ongoing high-quality, person-centred care despite the COVID19 pandemic. We will also share the potential for GC for other neurological conditions. drsuiwong@gmail.com 59